Temporal Quantitative Changes in the Resistant and Susceptible Wheat Leaf Apoplastic Proteome During Infection by Wheat Leaf Rust (Puccinia triticina) - Rampitsch, Christof; Huang, Mei; Djuric-Cignaovic, Slavica; Wang, Xiben; Fernando, Ursla (Frontiers in Plant Science, 2019)
Wheat leaf rust caused by the pathogenic fungus, Puccinia triticina, is a serious threat to bread wheat and durum production in many areas of the world. This plant-pathogen interaction has been studied extensively at the molecular genetics level however, proteomics data are still relatively scarce. The present study investigated temporal changes in the abundance of the apoplastic fluid proteome of resistant and susceptible wheat leaves infected with P. triticina race-1, using a label-free LC-MS-based approach. In general, there was very little difference between inoculated and control apoplastic proteomes in either host, until haustoria had become well established in the susceptible host, although the resistant host responds to pathogen challenge sooner. In the earlier samplings (up to 72 h after inoculation) there were just 46 host proteins with significantly changing abundance, and pathogen proteins were detected only rarely and not reproducibly. This is consistent with the biotrophic lifestyle of P. triticina, where the invading pathogen initially causes little tissue damage or host cell death, which occur only later during the infection cycle. The majority of the host proteins with altered abundance up to 72 h post-inoculation were pathogen-response-related, including peroxidases, chitinases, β-1-3-endo-glucanases, and other PR proteins. Five days after inoculation with the susceptible apoplasm it was possible to detect 150 P. triticina proteins and 117 host proteins which had significantly increased in abundance as well as 33 host proteins which had significantly decreased in abundance. The latter represents potential targets of pathogen effectors and included enzymes which could damage the invader. The pathogen-expressed proteins—seen most abundantly in the incompatible interaction—were mostly uncharacterized proteins however, many of their functions could be inferred through homology-matching with pBLAST. Pathogen proteins also included several candidate effector proteins, some novel, and some which have been reported previously. All MS data have been deposited in the PRIDE archive (www.ebi.ac.uk/pride/archive/) under Project PXD012586.